Pengaruh Investasi Nilai Impor Remitansi dan Suku Bunga Terhadap Gross Domestic Product - Nurachmat, Rahadian; Kurniawan, Mahrus Lutfi Adi; Cholida, Maya Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how the dependent variable (GDP) responds to the independent variable (investment import value, remittances, interest rates). The data used is secondary data, which can be obtained. from the central statistics agency (BPS), Bank Indonesia (BI). The data used in this research is quarterly, namely GDP data, direct investment, value of imports, remittances, interest rates for the period 2009-20022. The data analysis tool uses Autoegressive Distributed Lag (ARDL). The results of this research show that negative GDP -1 is not significant in the short term. Negative GDP -2 is not significantly significant, while in the short term GDP -3 is negative but significant. In the short term, investment is influential and not significant. on economic growth in the short term while in the long term investment Short The value of imports has no effect and is not significant in the short term while in the long term the value of imports has no effect and is not significant remittances are influential and significant remittances -1 has no effect but is significant but in the long term it is positive and significant interest rates have no significant effect. Interest rates -1 have an effect but are not significant, but in the long term interest rates have no effect but are significant. And the cumulative results show that the stability of the parameters on the blue line is still within the red line area, which can be said to be stable data stability.